Radiation damage of CsI:Eu crystals - Gektin, A.; Vasyukov, S.; Shiran, N.; Belsky, A. (Functional Materials, 2013)
The problems of radiation damage and afterglow nature for CsI:Eu crystal are discussed. It was determined that the luminescence parameters depend on the X-ray irradiation conditions. Irradiation leads to emission suppression at doses less than 100 Gy when the induced absorption was not observed yet. Hole (VF⁻ and I₃⁻) and activator′ color centers formation lead to partial decrease of the intrinsic UV and the activator luminescence, but it is not the dominating process of the radiation-induced phenomenon. The reverse dependences of afterglow and Eu²⁺ luminescence on irradiation dose were detected. Radiation induced luminescence quenching is determined by a modification of the activator centers structure.